The use of English discourse markers in the argumentative writing of EFL Indonesian and Thai University students: A comparative study - Wuwuh Andayani (JOURNAL OF EDUCATION, 2014)
The study aims to investigate the kinds of DMs employed by Indonesian and Thai students in their argumentative writing, to compare the use of DMs by both groups in terms of its nature and problems, and to find out whether the use of the DMs produced by Indonesian and Thai students contributes to the coherence of the text they write. The 46 argumentative writings composed by the Indonesian and Thai students were analyzed following Halliday and Hasan (1976) and Halliday and Matthiessen (2004). The findings of this study revealed that the most frequently used discourse markers was the addition ones (for Indonesian students) followed by concession and contrast, cause and result, and enumeration and order ones; and was the concession and contrastones (for Thai students), followed by addition, cause and result, and enumeration and order ones, respectively. In addition, it was also found that there were several problems in the use of DMs (i.e. the various type of the use of DMs, missing verbs in finite clauses, use of DMs in complex sentences, run-ons, overuse of the DMs, and repetition of the use of DMs) and were encountered differently by both groups of students. Moreover, this study also revealed that there was a relationship between the use of the DMs and text coherence. Finally, instead of being caused by the matter of the use of DMs, this study revealed that the incoherent text was also triggered by several problems including grammatical errors, irrelevant sentences, and out-of-topic sentences.